Blade row and blockage modelling in an axial compressor throughflow code - Thomas, Keegan D. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2005.